Taxonomic novelties from Cebu: a new species of Vaccinium (Ericaceae) and a new record of Phaius (Orchidaceae) for the Philippines - Salares, Val B.; Obico, Jasper John A.; Ormerod, Paul; Barcelona, Julie F.; Pelser, Pieter B. (Phytotaxa, 2018)
Vaccinium cebuense (Ericaceae) from Nug-as forest (Alcoy) and the Central Cebu Protected Landscape (Balamban), two of the last remaining forested areas of Cebu Island, Philippines, is here described as a new species. This species is unique among the known species of this genus in displaying a unique combination of characters: leaves with marginal glands that are spaced along the entire length of the leaf, anthers with distinct and recurved dorsal spurs, and petioles that are adaxially grooved. Our fieldwork in Nug-as also resulted in the discovery of Phaius reflexipetalus (Orchidaceae), a new record for the Philippines previously only known from Borneo. These and other recent taxonomic novelties emphasize the conservation importance of the few and small remaining forests of Cebu.